North Korea's hidden revolution how the information underground is transforming a closed society - Baek, Jieun (New Haven London Yale University Press, 2016)
One of the least understood countries in the world, North Korea has long been known for its repressive regime. Yet it is far from being an impenetrable black box. Media flow covertly into the country, and fault lines are appearing in the government's sealed informational boarders. Drawing on deeply personal interviews with North Korean defectors from all walks of life, ranging from military officers to diplomats, Jieun Baek tells the story of North Korea's information underground--the network of citizens who take extraordinary risks by circulating illicit content such as foreign films, television shows, soap operas, books, and encyclopedias. By fostering an awareness of life outside North Korea and enhancing cultural knowledge, the materials these citizens disseminate are affecting the social and political consciousness of a people, as well as their everyday lives" -- Front jacket flap.
Immortal gods: why North Korea is such a durable regime -- Cracks in the system: An information revolution -- "Old School" media: from trader gossip to freedom balloons -- The digital underground -- A new generation rising -- Implications, predictions, and a call to action -- Appendix. How remittances are sent to North Korea.
Includes bibliographical references and index.
Keywords: Mass media and cultured -- Korea (North); Mass media -- Korea (North); Popular culture -- Korea (North); Mass media and international relations; Mass media and propaganda; Korea (North) -- In mass media